PENGARUH DAMPAK PERCEPATAN VAKSINASI TERHADAP DINAMIKA PENYEBARAN COVID-19 UNTUK KESADARAN MASYARAKAT SEBAGAI DESA AMAN COVID-19 DESA TERATAI, KECAMATAN TABONGO, KABUPATEN GORONTALO - Asri Arbie; Abdul Wahidin Nuayi (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
This Community Service-Thematic Village Building activity aims to (1) Facilitate village and provide the latest data related to the Village SDGs as a starting point for formulating village development plans and (2) Communicating the latest data related to SDGs Village to the Village Government and submit it at the village meeting as initial material and data for the preparation/revision/development of the Village RPJM and Village RKP.Methods and technology for the implementation of the Thematic Community Service Program using two methods: methods, namely the Survey and Mentoring method. In terms of the results of the activities The targets for this Thematic-Village Development Community Service Program are: obtaining the latest village SDGs data in accordance with data collection provisions Ministry of Home Affairs